The Effect of Compensation and Work Discipline on Employee Work Productivity: Survey of PT. Daiwani Putra Utama Tasikmalaya Production Employees - Ai Faridah Nur Awwaliyah; Suci Putri Lestari; Mila Karmila (CV. Ulil Albab Corp, 2023)
This study aims to determine and analyze the effect of compensation and work discipline both simultaneously and partially on the work productivity of production employees at PT. Daiwani Putra Utama. The method used in this study is a survey. With a research sample of 70 production employees as respondents. The data used is using primary and secondary data. The analytical tool used in this study is multiple linear regression using the SPSS version 25 support application. The test results show that simultaneously the variables used in the study, namely compensation and work discipline, have a significant effect on the work productivity of employees in the production department at PT. Daiwani Putra Utama. Likewise, partially, there is a significant effect of compensation on the work productivity of employees in the production section, and partially, there is a significant effect between work discipline on the work productivity of employees in the PT. Daiwani Putra Utama.